THE REPRESENTATION OF THE DIVINE AND HUMAN BEING IMAGERY IN THE ENTITY OF RITUS SA’O NGAZA IN GURU SINA, NGADA, FLORES - Yohanes Vianey, Watu; Maryah, Emiliana; Parimartha, I Gde; Meko Mbete, Aron (E-Journal of Cultural Studies; Vol. 3, No. 1 Januari 2009)
This dissertation discusses the representation of the Divine and human being imagery in theentity of ritus Sa’o Ngaza in the village of Guru Sina in Ngada Regency, Flores. The empiricproblems of this dissertasion are connected with the marginalized phenomenon of the local religionthat submerged in the entity of ritus Sa’o Ngaza and its ritual practices. This probelm is relevant tobe investigated from the perspectives cultural studies.The problems raised in this study are : 1) the representation of the Divine and human beingimagery in the entity of ritus Sa’o Ngaza, 2) the representation of the relationhip between the Divineand human being in ritual practices of Sa’o Ngaza, and 3) the meaning of the representation of theDivine and human being imagery in the entity of ritus Sa’o Ngaza. This study applies the qualitativemethod and the data collection was done using techniques of intensive interview, participationobservation,and documentation. The data were analyzed using the theory of ritus, the theory ofprocess,the theory of semiotics, and the theory of deconstruction.The findings of the study can be explained as follows. Firstly, the representation of theDivine imagery is dyadic and triadic. In the dyadic imagery representation, The Divine is depicted as’The Giver of an Unlimited Love and at the same time as ’The Unpredictable Taker of Love’. In thetriadic representation, The Divine is depicted as The Sacred, in the attributive as ‘The Beginning’,‘The End’, and ‘The Present Throughout’. In the dyadic imagery, the human being consists of theelements of the body and the soul, and in the triadic imagery, the human being consists of theelements of the body, the psyche, and the spirit.Secondly, the relation between the Divine and human being is representatively revealed inthe ritual practices of legitimating Sa’o Ngaza. This relation centers in the methapor of relationshipbetween the simbolic body dan the religious body, and affirms the status of human being as ’thewrapper of divinity seed’ and ‘His image’.Thirdly, the meaning of the representation of the Divine and human being imagery in theentity of ritus Sa’o Ngaza is sacral , spiritual, and moral. The sacral value pertains to the dinamicrelationship between the human being and the Divine in a sacral way and the sacral place. TheSpiritual value pertains to the relation intra-human being and his spiritual opened and connectedthrough inner feeling with the One Sacral in the strong effort of making the human being perfect.The moral value pertains to a good relationship among human beings themselves in accordance withtheir norms of community.The findings of the study enrich the theory of process about the concept of the Divine fromWhitehead and contrast with the theory of ritus as the choreography of violence from Smedal. In theentity of ritus Sa’o Ngaza, there is a unique concept of human being in the design of ulu palicarvings, which describes the ideology of leadership in the local tradition. The finding of thisconcept can become the model of implementation of the decostruction theory and the semiotictheory which removes and deconstructs binary opposition between the leader (ulu) and the follower(eko).
Keywords: representation, imagery, entity, relation, meaning